2018
DOI: 10.1038/s41598-018-25936-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel canine circovirus strains from Thailand: Evidence for genetic recombination

Abstract: Canine circoviruses (CanineCV’s), belonging to the genus Circovirus of the Circoviridae family, were detected by next generation sequencing in samples from Thai dogs with respiratory symptoms. Genetic characterization and phylogenetic analysis of nearly complete CanineCV genomes suggested that natural recombination had occurred among different lineages of CanineCV’s. Similarity plot and bootscaning analyses indicated that American and Chinese viruses had served as major and minor parental viruses, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 47 publications
5
77
1
Order By: Relevance
“…Using the RDP package, a total of eight recombination events were detected in the canine CV sequences in this study. Previous studies have shown that recombination events can occur not only in the replicase gene [23] but also in other parts of the genome [22], which is in agreement with our results. In addition, this study also confirmed that intragenotypic and inter-genotypic recombination events have occurred.…”
Section: Discussionsupporting
confidence: 94%
“…Using the RDP package, a total of eight recombination events were detected in the canine CV sequences in this study. Previous studies have shown that recombination events can occur not only in the replicase gene [23] but also in other parts of the genome [22], which is in agreement with our results. In addition, this study also confirmed that intragenotypic and inter-genotypic recombination events have occurred.…”
Section: Discussionsupporting
confidence: 94%
“…Also, we found the presence of a unique mutation in the capsid protein (I371F) which is present in all Colombian strains sequence. No recombination events were obtained in the circulating CanineCv from Colombia, however previously reported recombination events were found 31 .…”
Section: Resultsmentioning
confidence: 73%
“…The putative recombinant served as a query to detect recombination with their parent lineages that derived from the RDP. The recombination analysis was modeled with a window size of 200 bp and step size of 20 bp 16,39 .…”
Section: Methodsmentioning
confidence: 99%